Kajian identifikasi faktor untuk pengembangan instrumen pengukuran kesiapan psikologis atlet atletik - Dwi Pramesti, Afifah; Hermahayu, Hermahayu; Faizah, Rayinda (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
In sports psychology, to improve athlete achievement, in addition to physiological factors, other factors influence an athlete's success, namely psychological factors. Psychological readiness is the readiness possessed by athletes before a match or during a match. Psychological readiness is one of the determining factors for the success of athletes in achieving achievements during matches. This study aims to analyze the determinants of the psychological readiness of athletic athletes. The research method uses descriptive qualitative methods with data collection techniques through focus group discussions. In the competition, psychological factors are needed more than physiological factors. This study showed that 90% of psychological factors affect performance in matches, and physiological factors influence 10%. This study found factors related to the psychological readiness of athletic athletes, namely coping, emotional regulation, self-regulation, and self-confidence. Athletes in training and competition need these factors. Problems that can disrupt the psychology of athletes in competing will result in achievements. This study's results can benefit trainers in integrating psychological approaches into physical exercise programs.